Production de cresson à haut risque dans les bas fonds d’Antananarivo ? - Marie-Hélène Dabat (Éditions en environnement VertigO, 2010)
Population growth and urban development in the South renew research topics on agriculture. Advantageous in some respects, urban agriculture entails many risks, especially those related to the quality of irrigation water and to urban farmers’practices. The article illustrates the case of Antananarivo, the capital of Madagascar, where watercress, which is highly appreciated by the consumers, had a growing development in the lowland of the city. This activity creates high income and can be practiced all around the year. However, health risks associated with its conditions of production are numerous : use of waste water and urban effluents, questionable practices of some farmers and traders. A multidisciplinary research program has studied this situation. A survey on consumption showed that methods used by households from Antananarivo for watercress preparation are suitable. Furthermore, microbiological analyses of the product at the production level and in households are reassuring. However, some issues remain unresolved. A qualitative survey reveals a duality in the image of the product : consumers are indeed shared between, firstly, their good appreciation of organoleptic and nutritional qualities of watercress and, secondly, their fear of disease related to the conditions of production they witness. The problem of safety is real because of the subjectivity of consumers that could, at worst, turn away from this product, at best, ask questions about the quality of their diet.